2003
DOI: 10.1074/jbc.m308080200
|View full text |Cite
|
Sign up to set email alerts
|

The Serine/Threonine Kinase Nek6 Is Required for Cell Cycle Progression through Mitosis

Abstract: The Aspergillus nidulans protein NIMA (never in mitosis, gene A) is a protein kinase required for the initiation of mitosis, whereas its inactivation is necessary for mitotic exit. Here, we demonstrate that human NIMA-related kinase 6 (Nek6) is required for mitotic progression of human cells. Nek6 is phosphorylated and activated during M phase. Inhibition of Nek6 function by either overexpression of an inactive Nek6 mutant or elimination of endogenous Nek6 by siRNA arrests cells in M phase and triggers apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
112
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 23 publications
9
112
0
2
Order By: Relevance
“…In previous studies, a prominent observed abnormality was prometaphase or metaphase arrest and an increase in the mitotic index (Yissachar et al, 2006;Kim et al, 2007;O'Regan and Fry, 2009). Similarly, interfering with the activity of Nek6 suggests that it is crucial for metaphase-toanaphase transition (Yin et al, 2003), whereas a reduction in the activity of Nek6/7 upstream regulator, Nercc1/Nek9, results in prometaphase arrest (Roig et al, 2002). Interestingly, Nek7-mutant MEFs did not exhibit prometaphase or metaphase arrest or an elevation in the mitotic index.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In previous studies, a prominent observed abnormality was prometaphase or metaphase arrest and an increase in the mitotic index (Yissachar et al, 2006;Kim et al, 2007;O'Regan and Fry, 2009). Similarly, interfering with the activity of Nek6 suggests that it is crucial for metaphase-toanaphase transition (Yin et al, 2003), whereas a reduction in the activity of Nek6/7 upstream regulator, Nercc1/Nek9, results in prometaphase arrest (Roig et al, 2002). Interestingly, Nek7-mutant MEFs did not exhibit prometaphase or metaphase arrest or an elevation in the mitotic index.…”
Section: Discussionmentioning
confidence: 86%
“…The indispensable developmental functions of Nek7 could be attributed to the complementary patterns of expression of nek6 and nek7, especially within the nervous system (Feige and Motro, 2002). At the cellular level, the cell cyclerelated phenotypes of nek7-targeted MEF cells, and the phenotypes of cells in which either Nek6 or Nek7 activity was downregulated (Yin et al, 2003;Yissachar et al, 2006;Kim et al, 2007;O'Regan and Fry, 2009) suggest nonredundant activities. The sequence of the Nek7 kinase targeting leads to polyploidy H Salem et al short N-terminal tail of the proteins is quite variable and can contribute to interactions with different substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nrk18p and Nrk20p are homologues of the mammalian Nek2, implicated in the splitting of duplicated centrosomes (Fry et al, 1998;Faragher and Fry, 2003). The second conserved subfamily includes human Nek6 and Nek7, which have been implicated in the metaphase-anaphase transition (Yin et al, 2003), and a single Tetrahymena homologue, Nrk32p.Two additional well supported subfamilies do not have animal homologues, but they include NRKs of Chlamydomonas (Bradley et al, 2004) and Tetrahymena and may be protist specific. The FA2 subfamily includes Fa2p and Cnk4p NRKs of Chlamydomonas and Tetrahymena Nrk8p, Nrk11p, and Nrk17p.…”
mentioning
confidence: 99%